Deciphering salt tolerance mechanisms in synthetic hexaploid and bread wheat under humic acid application: physiological and genetic perspectives - Alghabari, Fahad; Shah, Zahid Hussain (Frontiers in Plant Science, 2025)
Salt stress is a potential constraint that perturbs plant physiological and osmolytic processes, and induces oxidative stress. The plant biostimulant, such as humic acid (HA) is capable to improve the wheat-tolerance to salt stress through triggering the plant defense mechanisms and regulating the genetic determinants. In this context the present study has comparatively evaluated the effect of HA on salt tolerant synthetic hexaploid (SH) and salt susceptible bread wheat (BW) genotypes. The experiment was performed in three replicates using randomized complete block design (RCBD) having two factorial arrangements, with HA treatment as one, while genotype as second factor. HA treatment significantly enhanced chlorophyll (33.33%–100%) and photosynthesis (31.25%–50%), and significantly reduced the glycine betaine (GB) (42.85%–77.77%), proline (20%–28.57%) and Na+/K+ ratio (33.33%–50%) in salt stressed SH and BW genotypes. Additionally, HA significantly increase the activities superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT) by 57.14%–66.67%, 54.54%–83.33%, and 55.55%–80%, respectively in all salt stressed genotypes. The salinity associated genes TaNHX1, TaHKT1,4, TaAKT1, TaPRX2A TaSOD and TaCAT1 were upregulated, while TaP5CS was downregulated in SH and BW genotypes corresponding to their regulatory traits. Furthermore, the multivariate analysis including correlation, principal component analysis (PCA) and heatmap dendrogram further rectified the strong impact of HA on the strength of association and expression of stress marker traits. Overall, the SH genotypes showed more strong response to the HA and illustrated significant tolerance to salt stress based upon physiological, biochemical and genetic indicators. Conclusively, the SH can serve as a bridge to transfer alien genes associated with salt tolerance into elite bread wheat germplasm.